Notas sobre o Diario de una costurera proletaria de Victoria Guerrero (2024)
The article exposes a reading of the Diario de una costurera proletaria [Diary of a Proletarian Seamstress] (2013, with an expanded edition in 2018) by Victoria Guerrero Peirano. This book establishes a symbolic space for the manifestation of femininity, utilizing an art of poverty or a language of deficiency. Its aim is to narrate, through an autobiographical and documentary lens, the personal and collective experiences within the realm of work. For this study, concepts such as ‘extimate intimacy’ (Kamenszain), ‘disappropriation’, and ‘commonality’ (Rivera Garza) are utilized. These concepts provide a framework to analyze how Guerrero Peirano’s poetic compositions strive to articulate the experiences of working-class women. These women, whose fundamental rights have been violated by state bio/necropolitical regimes and various mechanisms of neoliberal capitalism, find a voice in her work.